(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper is devoted to the topic "Preparation and Study of a Butadiene Nitrile Polymer-Based Composition Using Astragals." Binary blends of butadiene nitrile rubber and astragals in various mass ratios were prepared, and the flow index of the alloy system was studied at temperatures of 130°C, 160°C, and 170°C and under loads of 12.0-21.0 kg. Our studies showed that at a temperature of 160°C and with an astragals content of 5 parts by weight in the binary blend, it acts as a modifier. As a result of the modification, the technological properties of NBR, primarily compatibility with other components and chemical stability, are increased by 1.5 times compared to standard modifying agents. An optimal formulation for producing rubbers based on butadiene nitrile and astragals was developed. A rubber compound based on an optimal formulation was prepared, and the vulcanization mode and time were determined. The resulting vulcanization temperature was 157°C, with a vulcanization time of 26 minutes. This work was conducted with the goal of acquiring a BNR-based rubber for cables that is chemically resistant to aggressive environments, more advanced, and fully capable of meeting operational specifications, exhibiting chemical resistance in saline areas, and suitable for use as a coating. The key parameters of the resulting mixture were determined using physical and mechanical methods and compared with standard rubbers, confirming that the proposed rubber's key parameters fully meet the standard requirements.